Financial Effectiveness and Efficiency Analysis of Magelang Regency After the Central Government’s Budget Efficiency Policy - Natta Sanjaya; Sigid Widyantoro; Anton Purwadi; Naufal Ridho; Raytanza Iswadinata (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This study analyzes the financial effectiveness and efficiency of Magelang Regency following the implementation of the 2025 central government budget efficiency policy. Using a mixed-method approach with sequential exploratory design, data were collected through interviews and budget reports. Quantitative analysis employed descriptive ratio methods to assess effectiveness and efficiency, while qualitative data explained the implementation dynamics. Results show that budget planning remained highly effective (99.56%) and efficient (27.76%), though capital expenditure absorption was only 4.02%. Internal audit, program prioritization, and disciplined reallocation supported fiscal stability despite reduced transfer funds. The study concludes that while the efficiency policy fostered fiscal prudence, it also slowed capital project execution. Findings suggest the need for balanced fiscal discipline and development acceleration.